Pengaturan cairan pada acute lung injury - Monalisa Elizabeth; Munar Lubis; Yunnie Trisnawati (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Mechanical ventilation is a life-saving technology for patients who develop acute lung injury (ALI) and investigators have conducted numerous investigations to determine the optimal support method and has been used for several decades. The incidence of ALI is quoted to be between 17 and 34 per 100,000 patients for year. Mechanical ventilation is indicated in patients with severe hypoxemia despite oxygen therapy, severe hypercapnia, or excessive work of breathing. Fluid management with the goal to obtain zero fluid balance in ARDS patients without shock or renal failure significantly increases the number of days without mechanical ventilation. Liberal and conservative fluid strategies are therefore complementary and should ideally follow each other in time in the same patient whose hemodynamic state progressively stabilizes.Key words : constipation; functional; children; medical therapy